FAKTOR-FAKTOR YANG MENENTUKAN KEPUTUSAN KONSUMEN MEMBELI KERAJINAN PERHIASAN PERAK DI PUSPA MEGA SILVER KABUPATEN GIANYAR - I Gusti Ayu Erma Sulistyani; Ni Made Hartini (Universitas Triatma Mulya, 2020)
This study aims to analyze the factors that determine the decision of consumers to buy silver jewelry crafts in Puspa Mega Silver, Gianyar Regency. The analysis technique used in this study is factor analysis. The variable used in this study is a single variable, namely the consumer's decision to buy silver jewelry crafts in Puspa Mega Silver, Gianyar Regency. The steps taken are distributing questionnaires to consumers who come to the Art Shop Puspa Mega Silver, Gianyar Regency and the sampling technique used is purposive sampling (determining the sample with certain considerations). The results obtained after analyzing the factors using SPSS from 12 statement items to analyze the factors that determine the decision of consumers to buy silver jewelery at Puspa Mega Silver, Gianyar Regency, from 12 statement items can be reduced to 4 factors including location factors with an eigenvalue of 4.955 and variance of 41.295%; product factor with eigenvalue of 1.741 and variance of 14.505%; product quality factors with eigenvalue of 1.222 and variance of 10.215% and personal factors with eigenvalue of 1.002 and variance of 8.335%. Based on the results of this study it has been seen that the factors that determine the decision of consumers to buy silver jewelry crafts in Puspa Mega Silver, Gianyar Regency are location factors, product factors, factors of product quality and personal factors. The most dominant factor on consumer decisions is the location factor of Puspa Mega Silver. Thus the advice taken into consideration in increasing sales of the company must maintain its location, make jewelry with quality materials with various variants and forms of silver jewelry. So that consumers feel happy and continue to buy jewelry products from Puspa Mega Silver, Gianyar Regency.